Factors explaining outstanding debt: the case for POS Malaysia Berhad Negeri Sembilan / Nur Huwaina Yunus - Yunus, Nur Huwaina (Faculty of Business and Management, 2009)
This study provides an analysis regarding to the “Factors Explaining Outstanding Debt: The Case for Pos Malaysia Berhad Negeri Sembilan” The purpose of this case study is to understand the concepts and elements of debt so it will help to determine the factors that contribute outstanding debts in Pos Malaysia Berhad Negeri Sembilan. At the end of this case study, participants will be able to identify appropriate techniques on collecting outstanding debts and understanding trade credit functions in helping the firms to success. In Pos Malaysia Berhad Negeri Sembilan, the collection of outstanding debt is very important as it show how effective and efficient does finance departments employees works in handling this problems. This study also tries to answer what are the effects that may arise in the delayed to collect debt from the customers. In order to analyze the issues, the data that have been use to collect the data are from primary and secondary sources.